Dynamic Finite Element Analysis of an Elevated Station-Track Structure Coupled System Under Resonance - Kai Cui; Lei Su (Tehnički Vjesnik, 2019)
In this study, an elevated station and the track structure are regarded as a coupled system, and the vibration performance of the entire system is analyzed under dynamic loading. Special attention is paid to the influence of the mechanical properties of parts of the system on its vibration performance. After a brief literature review of relevant studies on urban elevated rail transit vibration performance, a three-dimensional dynamic analysis model is established considering each component and the connections of the system; furthermore, modal analysis is applied to this model. Based on the model analysis, the vibration performance under harmonic vibration loads and moving train loads are analyzed separately. During the analysis of harmonic vibration, the effects of various parameters (e.g., rail pad stiffness, mass of elastic support block) on system vibration are considered.